Perceptions of the teachers and students of the College of Medicine of the Manila Central University on the critical thinking skills of students in a problem-based learning curriculum - Ong, Cesar M. (2003)
The latter half of the 90s have witnessed the introduction of Problem-based Learning (PBL) in Philippine medical schools. The approach is based on active learning in small groups with clinical problems as the stimulus for learning. One of the often-quoted advantages of the strategy is the development of critical thinking (CT) skills among the students. Objectives: The study was undertaken to describe the CT skills of students under the PBL curriculum of the Manila Central University - College of Medicine as perceived by their teachers and students themselves and to compare the perceptions of the teachers and the students. Methodolgy: This study is a descriptive research. All 323 students in the first three years of medical school, as of February 2002, and the 60 faculty members acting as tutors in the small group discussions were included in the study. Likert-type opinionnaire on six core CT skills (problem identification, problem description, problem exploration, applicability, integration and reflective thinking) was distributed to all students and tutors. Existing evaluation tools in the college, including the final examinations in three blocks, were also analyzed for CT skills. The responses of the teachers and students were compared and analyzed using the Mann-Whitney U test. The responses of the students and teachers across the year levels were similarly compared and analyzed using the Kruskal-Wallis test. Results: All 323 students and 40 tutors participated in the study. All students believed they demonstrated CT skills although they differ in their perceived strong and weak areas. The first year students had similar perceptions on the abilities to demonstrate applicability and to link ideas during problem exploration. The second year students shared similar perceptions in their reflective thinking skills. The third year students had similar perceptions on their skills to clarify concepts in problem description and reflective thinking. However, across the year levels, they have markedly different perceptions on their ability to demonstrate CT skills. Tutors in the first year had similar perceptions on the ability of their students to demonstrate all indicators of CT skills. Tutors in the second year shared this observation, except in the ability of the students to identify knowledge and skills from previously acquired information needed to solve problems. The only skills not observed by tutors in the third year were on the ability of the students to apply the present learning similar situations. Across the year levels, the tutors agreed that the students demonstrated these CT skills although not necessarily implying that they were becoming more evident from one year to the other. When the responses of the students were compared with the tutors, statistically significant differences were noted. If the core CT skills were considered, both students and teachers agreed that the students exhibited all six skills. However, the means of their responses were statistically difference. When existing tools were analyzed, the responses of the students during the peer- and self-evaluations were statistically different. The mean scores of the students three blocks on different year levels on analytical questions in their final examinations were similar to each other. Conclusions: CT can be measured by using indicators reflecting core skills. The students of the MCU-CM believed that they exhibited these skills. Their tutors believed that they exhibited these skills but were not as satisfied as the students. The students rated themselves lowest in justification as part of problem exploration, and highest in reflective thinking. The teachers did not see any statistically significant difference among these core skills in their students.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Critical thinking; Problem-based learning